Avaliação do acolhimento com classificação de risco em maternidades públicas no Nordeste do Brasil - VERAS, Patrícia de Sousa (2019)
The User Embracement and Risk Classification was idealized to be an effective tool and efficient in the searching for the quality improvement of the attendance in the urgency and emergency services and in the entrance door of maternity hospitals being essential to receive women in a respectful and qualified way, where the impersonal and bureaucratic attendance, by the order of arrival, will may impede serious cases of being properly identified and prioritized. The study tried to assess the reception with risk classification in maternity hospitals on the context of a Brazilian maternal and child health care network (Rede Cegonha) in Northeast region. It is an evaluative normative research, with quantitative delineation and use of primary data of the research entitled "Avaliação das Boas práticas na atenção ao parto e Nascimento em Maternidades da Rede Cegonha" (Evaluation of the good practices in the care to the childbirth and Birth in Maternity Hospitals of the "Rede Cegonha"). The sample of the study was composed by 175 maternity hospitals that performed 500 childbirth or more in 2015 with resourse from Rede cegonha, distributed in nine states. The data collection took place from December 2016 to September 2017 period. The level of implementation of the reception in obstetrics was considered implemented on maternity hospitals of Sergipe (75,01 to 100%) and partially implemented in other states of Northeast (50,1 to 75,00%). It was noted that the states of Bahia, Maranhão, Paraíba, Piauí, Rio Grande do Norte e Sergipe (75,01 a 100%) have an appropriate ambience to the execution of obstetrics reception, the states of Alagoas and Pernambuco (50,1 to 75,00%) have partially appropriate services and the state of Ceará has incipient ambience. It was identified that most part of maternity hospitals are of low complexity (80,6%), (80%) have at least 50 obstetric delivery bed and (77,7%) don't have Public-Private Sector Partnerships (PPP) rooms. Although the maternity hospitals have some good results as receptive and human ambience, privacy, safety and comfort to the companion reception. Also identified, that it has problems, especially in relation to the classification of obstetric risk of all the users and reference and counter-reference system. That way the success of The User Embracement and Risk Classification, as a proposal change of the templates of attention and management of the health practices, it exists the urgent need of reflection on the part of the protagonists of this procedure (managers, professionals and users).